SIMPEDAK: Mobile-based Active Blood Donor Information - Muhammad Zamroni Uska; Wirasasmita, Rasyid Hardi; Kholisho, Yosi Nur; Suryadiy, Muhammad Yusron (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
Palang Merah Indonesia (PMI), especially East Lombok Regency, is one of the main forces in providing blood stocks for patients in every hospital. However, there is a lack of voluntary blood donors so far, information about blood needs is only via online media, WhatsApp and Instagram groups. This research aims to produce a mobile-based Active Blood Donor Information System (SIMPEDAK) in East Lombok Regency, and determine the feasibility of material experts, media experts and user responses. This type of research is research and development using the waterfall model starting from the analysis, design, code & testing, implementation, maintenance stages. The subjects in this study were 46 people consisting of 20 PMI members, 16 students and 10 members of the general public or patient families to determine user responses. Data collection techniques use questionnaires and data analysis uses quantitative descriptive. The results of our findings are in the form of a mobile-based SIMPEDAK application or system. The results of the feasibility test for material experts were 92.75% (very feasible) and the results of the feasibility test for media experts were 96.66% (very feasible). Meanwhile, user response results received a score of 81.72% (very good). Thus, it can be concluded that this application is very suitable for use and has a high response as a mobile-based SIMPEDAK among blood donors and the wider community.